Kaposi sarcoma in an patient with atopic dermatitis treated with ciclosporin. - IRVINE, ALAN (My University, 2013)
There are four clinical subtypes of Kaposi sarcoma (KS): classic, endemic, epidemic and iatrogenic. The geographical prevalence of the endemic variant matches areas of human herpes virus type 8 (HHV8) seroprevalence. The iatrogenic variant, seen in immunosuppressed patients, can be associated with significant morbidity and mortality. This is the first report of KS described in the context of atopic dermatitis (AD) treated with ciclosporin (CSA). We report a case of KS in an HHV8 seropositive Congolese patient following immunosuppression with CSA for AD. Treatment has been challenging, protracted and associated with significant morbidity. Immunosuppressive therapies are increasingly used for inflammatory dermatological conditions, including AD. This case highlights the importance of HHV8 screening of patients from endemic regions or those with other risk factors. It also highlights the importance of early recognition of a condition associated with significant morbidity and even mortality to facilitate appropriate treatment.
PUBLISHED
Keywords: Kaposi sarcoma (KS); Immunology, Inflammation & Infection